1990
DOI: 10.1073/pnas.87.22.8697
|View full text |Cite
|
Sign up to set email alerts
|

Changing the invariant proline-30 of rat and Drosophila melanogaster cytochromes c to alanine or valine destabilizes the heme crevice more than the overall conformation.

Abstract: Drosophila melanogaster and rat cytochromes c in which proline-30 was converted to alanine or valine were expressed in a strain of baker's yeast, Saccharomyces cerevisiae, where they sustained aerobic growth. The mutations had no significant effect on the spectra or redox potentials but altered drastically the stability of the bond between the methionine-80 sulfur and the heme iron, as judged by four criteria: (i) the alkaline pKa values of the 695-nm band of the ferric form of the mutant proteins decreased by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 39 publications
4
26
1
Order By: Relevance
“…The main conclusion from these results is that some UP alterations, such as the ones we identified here, may play a role, albeit a relatively minor one, in VUR (see below). Specifically, the proline to alanine change in UP III could lead to the loss of a "proline-kink" thus resulting in a major change in protein conformation and possibly protein stability [36][37][38]. Although these results indicate that UP alterations can play a minor role in VUR, perhaps the most significant and somewhat surprising conclusion from our data is that major UP mutations are not found in patients with primary VUR.…”
Section: Discussionmentioning
confidence: 85%
“…The main conclusion from these results is that some UP alterations, such as the ones we identified here, may play a role, albeit a relatively minor one, in VUR (see below). Specifically, the proline to alanine change in UP III could lead to the loss of a "proline-kink" thus resulting in a major change in protein conformation and possibly protein stability [36][37][38]. Although these results indicate that UP alterations can play a minor role in VUR, perhaps the most significant and somewhat surprising conclusion from our data is that major UP mutations are not found in patients with primary VUR.…”
Section: Discussionmentioning
confidence: 85%
“…Some success was demonstrated by the increased stability of the Y67F mutant [12][13][14][15], but not with different Pro$! mutants [16], which lead to haem-crevice destabilization.…”
Section: Introductionmentioning
confidence: 99%
“…2329 Destabilization of the heme coordination loop is the likely explanation for the decreased pK a of the alkaline transition for several mutants of cyt c that target this loop, as well as for the presence of Lys-ligated conformers for cyt c in the presence of urea. 4 Mechanistic studies have suggested that deprotonation of a yet unknown “trigger” group precedes ligand replacement.…”
mentioning
confidence: 99%